2006
DOI: 10.2323/jgam.52.209
|View full text |Cite
|
Sign up to set email alerts
|

Studies on poly-β-hydroxybutyrate synthase activity of Nostoc muscorum

Abstract: IntroductionPoly-b-hydroxybutyrate (PHB) is a class of naturally occurring polyester which is produced and stored intracellularly in wide varieties of prokaryotes including cyanobacteria under unbalanced growth conditions (Anderson and Dawes, 1990;Stal, 1992;Steinbüchel, 1991). This polymer has attracted the researchers because of its potential to be an alternative to conventional plastics.The cyanobacterium, Nostoc muscorum accumulates PHB profoundly under conditions of nutrient (N and P) deprivation, mixotro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…It has been reported that acetyl-P can substitute for phosphoenolpyruvate as the phospho donor for purified enzyme I of the phosphoenolpyru- VOL. 189, 2007 INTRACELLULAR ACETYL PHOSPHATE MEASUREMENT 5579 vate:carbohydrate phosphotransferase system (15) and can act as an allosteric effector for HPr kinase/phosphatase purified from the gram-positive organism Bacillus subtilis (41), for certain eukaryotic ATPases (7,22,49), and for poly-␤-hydroxybutyrate synthase from cyanobacteria (35,46). To the best of our knowledge, however, there have been no reports demonstrating that any of these interactions can occur in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that acetyl-P can substitute for phosphoenolpyruvate as the phospho donor for purified enzyme I of the phosphoenolpyru- VOL. 189, 2007 INTRACELLULAR ACETYL PHOSPHATE MEASUREMENT 5579 vate:carbohydrate phosphotransferase system (15) and can act as an allosteric effector for HPr kinase/phosphatase purified from the gram-positive organism Bacillus subtilis (41), for certain eukaryotic ATPases (7,22,49), and for poly-␤-hydroxybutyrate synthase from cyanobacteria (35,46). To the best of our knowledge, however, there have been no reports demonstrating that any of these interactions can occur in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…The activity of PHB synthase was determined using the method of Sharma et al (2006) who measured the absorbance of CoA at A 412nm . The activity of glucose-6-phosphate dehydrogenase (G6PD) was analysed by measuring the released NADPH at A 340nm (Sagisaka 1972).…”
Section: Measurement Of Enzyme Activitiesmentioning
confidence: 99%